Research trends of aqua medicines, drugs and chemicals (AMDC) in Bangladesh: the last decade's (2011-2020) story to tell (Asian Journal of Medical and Biological Research, 2021)
Aquaculture medicines, drugs, and chemicals or simply AMDC, are critical in protecting aquaculture farmers from disease in farmed animals and economic losses. The AMDC is now a well-established industry in Bangladesh, and each year, new products that benefit farmers are launched. This review examined published research information on AMDC over the last decade (2011-2020) and discovered that 41 research publications from various parts of Bangladesh were published, citing the names of 1484 AMDC products. It was discovered that 19 generic antibiotics are well established and widely used in different regions' aquaculture, including shrimp aquaculture. Although some researchers expressed concern about the use of antibiotics in aquaculture, they believe that with proper withdrawal periods and the application of small doses, farmers may avoid economic losses. However, the pathway of the antibiotic introduction in aquaculture setup in Bangladesh was unknown to the researchers, through this review, we revealed the pathway of antibiotics introduction in aquaculture. Additionally, this review revealed that various AMDC products, including oxygen suppliers, growth promoter supplements, disinfectants, raw chemicals, probiotics, pond preparation and management AMDC, and toxic gas removal AMDC, are readily available in various markets throughout Bangladesh. The observation implied that research on the efficacy of various AMDC products in Bangladesh's agro-ecological zones could be conducted, which would aid researchers in deciphering the true nature of AMDC in sub-tropical climates.Asian J. Med. Biol. Res. 2021, 7 (2), 90-106